2021
DOI: 10.3389/fonc.2021.678966
|View full text |Cite
|
Sign up to set email alerts
|

EGFR and PI3K Pathway Activities Might Guide Drug Repurposing in HPV-Negative Head and Neck Cancers

Abstract: While genetic alterations in Epidermal growth factor receptor (EGFR) and PI3K are common in head and neck squamous cell carcinomas (HNSCC), their impact on oncogenic signaling and cancer drug sensitivities remains elusive. To determine their consequences on the transcriptional network, pathway activities of EGFR, PI3K, and 12 additional oncogenic pathways were inferred in 498 HNSCC samples of The Cancer Genome Atlas using PROGENy. More than half of HPV-negative HNSCC showed a pathway activation in EGFR or PI3K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…However, tumors might exhibit accelerated MEK-ERK pathway activity despite missing MAPK pathway mutations due to the activation of upstream regulators (e.g., EGFR) by genomic alterations or high levels of stimulating ligands [78]. This assumption is in line with computational inferred pathway activities, which are not necessarily associated with the mutational landscape of key components in the respective pathways as demonstrated recently for EGFR or PI3K pathways [78,79].…”
Section: Discussionsupporting
confidence: 59%
“…However, tumors might exhibit accelerated MEK-ERK pathway activity despite missing MAPK pathway mutations due to the activation of upstream regulators (e.g., EGFR) by genomic alterations or high levels of stimulating ligands [78]. This assumption is in line with computational inferred pathway activities, which are not necessarily associated with the mutational landscape of key components in the respective pathways as demonstrated recently for EGFR or PI3K pathways [78,79].…”
Section: Discussionsupporting
confidence: 59%
“…After annotation by the GTF files, 545 DNA repair genes were eventually used for subsequent analyses. GSE41613 (15), GSE27020 (16), GSE117973 (17), and GSE65858 (18) datasets with transcriptome and clinical data of patients with HNSCC were downloaded from Gene Expression Omnibus (https://www. ncbi.nlm.nih.gov/geo/) for external validation.…”
Section: Data Downloadmentioning
confidence: 99%
“…This current study showed that the EGFR, PI3K, and NF-κB signaling is downregulated and upregulated in PCa by USP8 silencing and overexpressing, respectively ( Figure 4 ). Moreover, PI3K/Akt is a well-established downstream target of EGFR, which is generally activated by EGFR autophosphorylation leading to cell proliferation and growth ( 33 35 ). However, the underlining mechanism of USP8 in regulating EGFR and PI3K targeting to activate the NF-κB signaling pathway in PCa is not clearly stated yet.…”
Section: Resultsmentioning
confidence: 99%